Self-Reported Onset of Paroxysmal Atrial Fibrillation Is Related to Sleeping Body Position - Gottlieb, Lisa A.; Blanco, Lorena Sanchez y; Hocini, Mélèze; Dekker, Lukas R. C.; Coronel, Ruben (Frontiers in Physiology, 2021)
Background: Because stretch of the atrial myocardium is proarrhythmic for atrial fibrillation (AF), and a left lateral body position increases atrial dimensions in humans, we hypothesized that left lateral recumbence is a frequent AF-triggering body position in AF patients. Methods: We performed a questionnaire study of symptomatic paroxysmal (episodes of AF < 1 week) AF patients scheduled for a first AF ablation therapy at Catharina Hospital, Eindhoven, the Netherlands and at University Hospital, Bordeaux, France. Results: Ninety-four symptomatic paroxysmal AF patients were included (mean age 61±11 years, median AF history of 29[48] months, 31% were females). Twenty-two percent of patients reported a specific body position as a trigger of their AF symptoms. The triggering body position was left lateral position in 57% of cases, supine position in 33%, right lateral position in 10%, and prone position in 5% (p=0.003 overall difference in prevalence). Patients with positional AF had a higher body mass index compared to patients without nocturnal/positional AF (28.7[4.2] and 25.4[5.2] kg/m2, respectively, p=0.025), but otherwise resembled these patients. Conclusion: Body position, and the left lateral position in particular, is a common trigger of AF in symptomatic AF patients. Moreover, positional AF is associated with overweight. Understanding of the underlying mechanisms of positional AF can contribute to AF treatment and prevention.